La mort vivante ou le corps intercesseur (société maure-islam malékite) - Corinne Fortier (Revue des Mondes Musulmans et de la Méditerranée)
In this article, images and practices related to death are examined through a reading of Islamic scriptural sources as well as through their inscription in a specific society, the Moorish society of Mauritania. In moving from the field to the texts, a detailed analysis of funerary rites and of the status given to the dead allows us to interrogate the Islamic sources on the same subjects. And in an inverse movement, drawing connections between local practices and the foundational texts of Islam will reveal the subtle and multi-faceted negotiation carried out between a Muslim society and its scriptural references.Through this analysis, the majority of funerary practices will be shown to have a salvational effect for the deceased, but also for those who carry out these rites. It appears, therefore, despite some rejection of intercessory practices in Islam, that the dead in this religion are considered to be mediators between men and God. In addition, the living continue even long after the funeral to seek the salvation of their relations souls and, more generally, those of all Muslims. This shows that the living can also influence the destiny of the dead, ultimately decided by God.